Establishing new grasslands on crop fields: short‐term development of plant and arthropod communities. Issue 8 (3rd March 2022) - Hussain, Raja I.; Brandl, Manuela; Maas, Bea; Krautzer, Bernhard; Frank, Thomas; Moser, Dietmar
Abstract : Establishment of semi‐natural grasslands offers a valuable approach to the conservation of threatened grassland biodiversity. We established new grassland strips on former crop fields adjacent to old semi‐natural grasslands and monitored the development of plant, carabid, spider, and wild bee communities over 3 years. The studied plant and arthropods communities were significantly different between newly established grassland strips and old grassland. Our results suggest that restoring plant and arthropod communities takes longer than 3 years to become similar to old semi‐natural grasslands.